Respuesta :

Answer:

C.) [tex]\frac{a^6}{b^5}[/tex]

Step-by-step explanation:

[tex]\frac{a^2b^{-7}}{a^{-4}b^{-2}}[/tex]

Use the quotient rule [tex]\frac{x^a}{x^b}=x^{a-b}[/tex] :

[tex]a^{2+4}b^{-7+2}\\\\a^6b^{-5}\\\\[/tex]

Use the negative power rule [tex]x^{-a}=\frac{1}{x^a}[/tex] :

[tex]a^6*\frac{1}{b^5}\\\\\frac{a^6*1}{b^5}\\ \\\frac{a^6}{b^5}[/tex]

:Done

Answer:

D

Step-by-step explanation:

[tex]\dfrac{a^2b^{-7}}{a^{-4}a^{-2}}=\\\dfrac{a^2}{a^{-4}}\cdot \dfrac{b^{-7}}{b^{-2}}=[/tex]

[tex]a^6b^{-5}[/tex], or option D. Hope this helps!

ACCESS MORE